ANALYSIS OF THE POSSIBILITY OF REPLACING THE ВНІІНП -286M LUBRI-CANT ON THE AERO SHELL GREASE 33 IN THE HIGH LIFT DEVICES OF THE WING OF THE AN-FAMILY AIRCRAFT - Якобчук, Олександр Євгенійович (Problems of Friction and Wear, 2020)
The problem of ensuring the lubrication of gearboxes of high lift devices in aircraft of the AN family is considered. Modern aircraft are equipped with a large number of electromechanical elements with the possibility of remote control. In all these cases, there is a mechanical component, and accordingly, the relative movement of one element relative to another, all this causes the presence of friction processes in these mechanical systems. To ensure reliable, continuous, long-term operation of friction pairs using lubricants. In the work of aeronautical engineering is a special feature - work in different operating conditions. These can be critical conditions associated with node overloading, sudden changes in temperature, the use of low-quality lubricant. In modern conditions, the issue of the quality of materials for the production and maintenance of aeronautical engineering is not at a high level. First of all, this is due to improper transportation, storage, reloading and refilling of lubricant. Under these conditions, lubricants are able to accumulate moisture. This phenomenon leads to watering of the lubricant, and, accordingly, changes in the physicochemical properties of lubricants due to their watering. All this leads to increased wear of parts of the units, as well as to an early replacement of the lubricant when it is flooded, which significantly increases operating costs. In turn, analysis of the effect of different water concentrations on anti-wear and anti-friction properties of lubricants considered in the work, showed that the use of Aero Shell Grease 33 lubricant reduces wear of 30ХГСА steel (leading and lagging surfaces), regardless of water concentration ЕРА ВНІІНП -286M. The state of use of the lubricant is analyzed to ensure reliable operation of the wing mechanization gearbox. The correct approach when choosing a lubricant is quite complicated and important. It is proposed to replace the ВНІІНП -286M lithium grease with Aero Shell Grease 33. The effect of different water concentrations on the antiwear and antifriction properties of lithium greases is analyzed.